PENGARUH JENIS KOMPOS TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG MANIS (Zea mays saccharata Sturt) - Syafriliandi ' '; Murniati ' '; Idwar ' ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The research aims to determine the effect of type of compost, and know the kind of good compost for the growth and production of sweet corn (Zea mays saccharata Sturt). This research was conducted at the experimental farm of the Faculty of Agriculture, University of Riau in May to August 2015. This study used a completely randomized design (CRD), which consists of six treatments, each treatment was repeated 4 times to obtain 24 units of the experiment, while the treatment is given is Ko (without compost), K1 (10 ton / ha compost cassava peel), (10 tons / ha of compost PEFB), (10 tons / ha of rice straw compost), and (10 ton / ha maize straw compostg). Parameters measured were plant height, leaf length, leaf width, stem diameter, while the male flowers appear, while the female flowers appear, cob length, cob diameter, number of rows / ear, seed number / line, and the weight of variance followed cob.The reanlted by Duncan test New Multiple Range test at 5% level. The results showed that the administration of the various types of compost (cassava peel, PEFB, rice straw, water hyacinth and corn straw) significant effect on all parameters (plant height, leaf length, leaf width, stem diameter, time appears the male flowers, time appears flower female, cob length, cob diameter, heavy cob without husks, seed number per line and number of lines per cob) on the growth and yield of sweet corn. Giving compost cassava peel with a dose of 10 ton / ha gives better results on the growth and yield of sweet corn. It can be seen from all the parameters observed. Keywords: Sweet corn, compost (cassava peel, PEFB, rice straw, corn straw and water hyacinth)